Teaching Radiology to Medical Students in Canada; a Virtual, Integrative, Clinical Approach. Issue 2 (May 2022) - Kamel, Serageldin; Dobson, Jessica L.; Patel, Parth; Khatchikian, Aline D; Rohren, Scott A; Cheung, Jeffrey Lam Shin; Rooprai, Paul; Gorman, Mathew; Tomasso, Daniel; Greidanus, Paul; Xiong, Wei Ting; Kielar, Ania; et al.
Purpose: To construct, apply, and evaluate a multidisciplinary approach in teaching radiology to Canadian medical students. Methods: A multidisciplinary team of radiology and other disciplines experts designed an online 5-session course that was delivered to medical students. The topics of each session were clinical cases involving different systems. The target audience was medical students of Canadian schools. Pretests and post-tests were administered before and after each session respectively. An evaluation survey was distributed at the end of the course to gauge students' perceptions of this experience. Results: An average of 425 medical students attended the live sessions. For each session, 405 students completed both the pre-tests and post-tests. In general, students scored an average of 56% higher on the post-test than on the pre-test. The final course survey was completed by 469 students. The survey results show that more than 98% of students found the course to meet or exceed their expectations. Over 80% of students agreed that the course increased their interest in radiology and about 81% agree that the topics presented were excellent and clinically important. The ratings in the final survey results also indicate that students increased their confidence in basic radiology skills after completing the course. Conclusions: The implementation of an integrative clinical approach to teaching radiology in a virtual setting is achievable. It provides efficient use of educational resources while being accessible by a large number of students across different medical schools.